Influence Service Quality and Customer Relationship Marketing to Customer Value and it’s implications for Customer Satisfaction in Branch Office BRI Bandung - Henny Noviany (Fakultas Bisnis, 2020)
This study aims to determine the effect Service Quality and Customer Relationship Marketing to Customer Value and it’s implications for Customer Satisfaction in Branch Office BRI Soekarno Hatta Bandung. The population in this study were customer who have used banking service in BRI, while the sample in this study was 100 respondents using purposive sampling technique. Data analysis technique used is the technique Correlation Analysis (Path Analysis) to determine the degree of closeness of the relationship between variables. The results showed that effect direct Service Quality for 0379. Service Quality indirect effect through the CRM of 0.149. CRM direct influence on Customer Value of 0.092 and indirectly influence the CRM through Service Quality of 0.149 so that the total effect of 0771. The direct effect of Customer Value on Customer Satisfaction of 0,816. The results show determination coefficient of 77.1% and 22.9% Pye, and partial variable Service Quality more dominant effect of the variable CRM. Obtained the conclusion that the effect of Service Quality have the greatest influence. Customer Value showing determination coefficient of 81.6% and 18.4% Pye, from satisfaction to Customer Satisfaction variable.